EPID-04. PREDCAP, the French registry of predisposition to pediatric cancers. (3rd June 2022) - Guerrini-Rousseau, Lea; Hoarau, Pauline; Bougeard, Gaelle; Golmard, Lisa; Colas, Chrystelle; Gauthier-Villars, Marion; Houdayer, Claude; Frebourg, Thierry; Bourdeaut, Franck; Brugieres, Laurence
Abstract: A pathogenic or likely pathogenic variant (PV) in a major cancer predisposition gene is identified in almost 10% of children or young adults who developed a cancer, regardless of their family history. This incidence may increase by the development of wide tumor sequencing programs leading to identify germline PVs in cancer patients and new cancer predisposition syndromes (CPS) associated with childhood cancers. Due to the rarity of each CPS, we still lack information about phenotype associated with most CPS especially cancer risks according to age as well as tumor characteristics and response to treatment. Within the French genetic multidisciplinary network involving pediatric oncologists, oncogeneticists and researchers, we have created a clinico-molecular registry for pediatric-CPS according to data protection regulation. The PREDCAP database collects clinical, genetic and molecular data from patients who developed pediatric tumors associated with a CPS, both retrospectively and prospectively. It includes a mandatory set of data on clinical phenotype, tumor characteristics (including treatment and outcome), family data and results of genetic analyses, with annual data updates. Interoperability with existing databases is planned, allowing for pooling of data collection and management. Aims of PREDCAP registry are to obtain reliable clinical and molecular data on pediatric CPS with a simplified and effective access. By collecting all available data on a large number of patients thanks to international collaborations, we hope to improve the knowledge on rare CPS, in particular, to better define the tumor spectrum and the penetrance of PVs, to analyze the specificity of tumors associated with these germline PVs. With this tool, we wish to facilitate future projects using structured and centralized data, associated with a virtual bank of available tumor and constitutional DNA, to evaluate and improve the relevance of management recommendations established for each syndrome.